2021
DOI: 10.1016/j.jneuroim.2020.577468
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone and thyromimetics inhibit myelin and axonal degeneration and oligodendrocyte loss in EAE

Abstract: We have previously demonstrated that thyromimetics stimulate oligodendrocyte precursor cell differentiation and promote remyelination in murine demyelination models. We investigated whether a thyroid receptor-beta selective thyromimetic, sobetirome (Sob), and its CNS-targeted prodrug, Sob-AM2, could prevent myelin and axonal degeneration in experimental autoimmune encephalomyelitis (EAE). Compared to controls, EAE mice receiving triiodothyronine (T3, 0.4 mg/kg), Sob (5 mg/kg) or Sob-AM2 (5 mg/kg) had reduced c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…As represented by previous studies, Triiodo-L-thyronine (T3), which is one of the differentiation medium ingredients, controls the specification and differentiation of OPCs to the mature oligodendrocytes. T3 promotes and helps the timing of precursor cell differentiation through a currently unknown mechanism [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…As represented by previous studies, Triiodo-L-thyronine (T3), which is one of the differentiation medium ingredients, controls the specification and differentiation of OPCs to the mature oligodendrocytes. T3 promotes and helps the timing of precursor cell differentiation through a currently unknown mechanism [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord sections co-stained with DAPI and TREM2 antibodies in the dorsal white matter of the lumbar 5D). Immunohistochemical analysis of this same spinal cord region showed that the population of CD11b-positive cells, which correspond to microglia and/or macrophages, was not statistically different between Sob-AM2-treated and vehicletreated mice (see Figure S2) (Chaudhary et al, 2021). This indicates that the increase in TREM2 staining was not a result of increased myeloid cells in the spinal cord lesions.…”
Section: Resultsmentioning
confidence: 85%
“…The autoimmune insult in EAE produces demyelination and axonal degeneration, particularly in the lumbar spinal cord region in mice. We have shown previously that, in mice with EAE, T3, sobetirome, and Sob-AM2 treatment improves clinical disease scores, and reduces demyelination and axonal degeneration within the spinal cord (Chaudhary et al, 2021). Thus, the question arises as to whether this results in part from thyromimetic stimulation of the TREM2 signaling pathway in microglia and macrophages to produce an anti-inflammatory phenotype, and induce phagocytosis of myelin debris, which is known to be a prerequisite to myelin repair (Lloyd and Miron, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These results can be explained by the influence of disregulation of thyroid hormone. In normal conditions, thyroid hormone show the ability of regulating neural cell proliferation, migration and myelination, as well as protecting neuroglial cells from pathological death in the central nervous system ( Hartley et al, 2019 ; Chaudhary et al, 2020 ). In TAO patients, increased thyroid hormone can induce damage of neuron and glial cells, disrupting cell functions and the homeostasis of dopaminergic neuron activity, which might lead to neural complications ( Atterwill et al, 1984 ; Cheng et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%